Some Physical and Motor Abilities and Their Contribution to The Scoring Skill of Futsal Players - Thaer Dawood Salman; Assad Lazem Ali; Nidaa Yasir Farhood (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The game of futsal requires physical and motor abilities in order to perform it, as these abilities play a fundamental role in making the player have a wonderful physical level and be able to implement the skill aspect of futsal football, especially the scoring skill, which is the subject of the study. The importance of the research lies in arriving at knowledge of the percentage The contribution of some physical and motor abilities to the performance of the scoring skill in indoor soccer, in order to reach final scientific results that serve researchers, coaches, and players alike. The research aims to identify the most important physical and motor abilities of young players in futsal football, and to identify the percentage of contribution of some physical and motor abilities in terms of the performance of the scoring skill in futsal football for young players. Tests were conducted on (260) players from the youth and sports forums in Baghdad Governorate for the sports season. 2023-2024 AD. Four tests were used to measure explosive power, speed of response, agility and flexibility, in addition to the scoring skill in futsal. After processing the data, it was concluded that there is a contribution percentage for the test (vertical jump from stability) as one of the indicators of physical and motor abilities along with the scoring skill. In futsal, there was a percentage of contribution to the tests (vertical jump from stability and Nelson for transitional motor response) as one of the indicators of physical and motor abilities with the skill of scoring in futsal, by (2.3%), and there was a percentage of contribution to the tests (vertical jump from... Stability and Nelson for the transitional motor response and Semo for agility) as one of the indicators of physical and motor abilities, with scoring skill in futsal amounting to (9.3%) , and a contribution percentage for the two tests (vertical jump from stability and Nelson for the transitional motor response and Semo for agility, sitting and arm extension) as one of the ability indicators. Physical and motor skills with scoring skills in futsal reached (9.4%).